Effect of malaria infection on hematological profiles of people living with human immunodeficiency virus in Gambella, southwest Ethiopia. Issue 1 (December 2017) - Sahle, Tsion; Yemane, Tilahun; Gedefaw, Lealem
Abstract Background Malaria and human immunodeficiency virus are the two most devastating global health problems causing more than two million deaths each year. Hematological abnormalities such as anemia, thrombocytopenia and leucopenia are the common complications in malaria and HIV co-infected individuals. The aim of this study was to determine the effect of malaria infection on hematological profiles of people living with HIV attending Gambella Hospital ART clinic, Southwestern Ethiopia. Objective To determine the effect of malaria infection on hematological profiles of people living with HIV attending Gambella Hospital ART clinic, Southwestern Ethiopia. Methods A facility based comparative cross-sectional study was conducted from May 25 to November 11, 2014 in Gambella Hospital. A total of 172 adult people living with HIV (86 malaria infected and 86 malaria non-infected) participants were included in the study. Demographic, anthropometric and clinical data were collected. Venous blood samples and stool specimen were collected for laboratory analysis. Microscopic examination of peripheral blood films was done for detection of malaria parasites. Descriptive statistics, student T- test, bivariable and multivariable analyses were performed using SPSS V-20. Statistical significance was set atp < 0.05. Results A total of 172 adult people living with HIV were included in the study. The prevalence of anemia, thrombocytopenia and leucopenia in malaria and HIV co-infected participants were 60.5%, 59.3%, and 43.0%, respectively. Resident (AOR: 4.67; 95% CI: 1.44, 15.14), malaria infection (AOR: 2.42; 95% CI: 1.16, 5.04) and CD4 + count were predictors for anemia. A predictor for thrombocytopenia was malaria infection (AOR: 9.79; 95% CI: 4.33, 22.17). Malaria parasitic density (AOR: 0.13; 95% CI: 0.03, 0.57) and CD4 + count (AOR: 4.77; 95% CI: 1.23, 18.45) were predictors of leucopenia. Conclusions Findings suggest that the prevalence of anemia and thrombocytopenia were significantly higher in the malaria and HIV coinfected participants than the HIV mono-infected participants. Mean values of hematological profiles were significantly different in the two groups. Future prospective studies with larger sample size from other settings are needed to substantiate the findings.